Обучение научному стилю русского языка с учетом культурных особенностей речевого общения - Ирина Бакланова (Studia Rossica Posnaniensia)
The linguistic features of Russian scientific and educational texts are compared from the point of view of Grice’s conversational maxims. This article shows that many stylistic mistakes in students’ research papers result from these students’ use of educational, and not scientific style, while the former is targeted at a different kind of reader.